Institutional Development of Family-owned Businesses in Japan: A European Perspective - Jan K.Solarz (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
From the European perspective the institutional development of family-owned businesses in Japan has come full circle. Beginning in the XVII century with a strong separation of aristocrats, samurais, traders, peasants families, and through to the creation of the zaibatsu and keiretsu to the rise of Japan Inc.- there has been one successful and equal family. Now Japanese families are again separated and unequal in their everyday life. In this context it should be expected to witness a rise of, more innovative and entrepreneurial, family-owned businesses. Both Japan and Europe are family-oriented societies and economies. Demographic changes create challenges to family-owned businesses in Japan as well as in Europe. What we can learn from the institutional development of family-owned businesses in Japan? Answers to this question are especially valid in Poland, which is as nationally homogeneous as is Japan. Both Poland and Japan are also bank-oriented financial systems. Are these financial systems friendly to a familyowned business? In Europe creation the of capital markets are seen as an institutional innovation that is friendly to a family-owned business. In Japan both historical legacy and the social structure limit the development of capital markets. The institutional and comparative perspective on family-owned businesses in Japan contributes towards the discussion of the phenomena of entrepreneurship and development.